From high performance target to social destabilization: Analyzing doping drugs overdose among young manual workers in Northern Benin - Imorou, Abou-Bakari (International research journal of management, IT and social sciences, 2020)
This research work seeks to understand the mechanisms through which doping drug overdose gradually leads to social destabilization construct among young rural workers in Northern Benin. Regarded as high-risk behaviors spreading among the active youth, the inappropriate consumption of doping drugs turns out to become a source of public health problems among the majority of farming communities. The sociologically-oriented brainstorming sprouting from this research paper emerges as a result of an ethnographic study drawing on the qualitative research paradigm. It considers the risk perceptions issue in a social environment divided between the local social values conservation and hard work-driven productivity. The analyzed data are collected following long sequences of observations fitted in between by several individuals and focus groups interviews. The households are adopted to serve not only as observation units but also as spaces where the young over users of doping drugs socialize. Therefore, the young manual workers become bogged down in the new momentum giving rise to new social profiles the success of which depends on the overuse of performance-enhancing drugs.